Frequency, characteristics and outcomes of appendicular neuroendocrine tumors: A cross-sectional study from an academic tertiary care hospital. (September 2017) - Abdelaal, Abdelrahman; El Ansari, Walid; Al-Bozom, Issam; Khawar, Mahwish; Shahid, Fakhar; Aleter, Ammar; Abunuwar, Mohammed Rasoul; El-Menyar, Ayman
Abstract: Background: Appendicular neuroendocrine tumors (NET, Carcinoid tumors) of the appendix are rare and mostly diagnosed incidentally on the post-operative histopathological examination. NET are usually associated with good 5-year survival rates. We aimed to assess our experience for the diagnosis and management of NET over 11 years. Method: It is a retrospective chart review of all clinically suspected patients with acute appendicitis who underwent emergent appendectomy with intention to treat between January 2004–December 2014, and were clinically followed up until 2016. Results: During the study period, a total of 13641 patients underwent emergency appendectomy, of which 32 were histologically confirmed NET. The mean age of the NET cases was 25.3 ± 7.9 years; 78% were males and all were clinically presented with acute appendicitis. The mean leucocyte was 15 ± 14 × 10 9 per Liter, and mean tumor size was 4.86 ± 3.18 (ranged 1.5–13) mm. The median length of hospital stay was 4 (2–15) days. One patient had right hemicolectomy; diagnosed with right colonic cancer with NET being an incidental finding as part of histopathological assessment. Another patient required a second stage procedure; he was diagnosed as goblet cell carcinoid with positive margin. None of the patients died 30-day postoperatively and all of them survived on clinical follow-up that ranged between 2 and 13 years. Conclusion: Carcinoid tumors of the appendix are rare and typically diagnosed incidentally. Detailed examination of routine appendectomy specimens is the key for diagnosis. Simple appendectomy suffices for tumors <2 cm for adequate clearance. Appendicular carcinoid tumors are associated with good long-term outcomes.